Costos de producción y comercialización de productores de acopio lechero Tahualag, Cantón Guano, Provincia de Chimborazo 2023. - Padilla Meléndrez, Wilson Fabián (2024)
This study analyzes the production and marketing costs of cold raw milk at the Tahualag dairy collection center, Guano Canton, Chimborazo Province during 2023. The general objective is to estimate these costs, with specific objectives of determining the production capacity, analyzing productivity and develop an econometric model that explores the relationship between production and marketing costs. The methodology includes surveys of the center's 20 producers, who constitute 100% of the target population. These producers are also involved in other agricultural activities, providing a comprehensive view of the center's business practices. The main hypothesis suggests that the costs managed b y the center are efficient and generate economic benefits. The variables studied cover the cost of raw material production, maintenance cost and the production cost per liter of milk. The results indicate a notablevariability in production costs among producers, as well as in the cost per liter of milk. Linear regression shows that daily production has a limited impact on daily total cost, which implies the influence of other factors such as operational efficiency and resource management on costs.